Health disparity with light on oral health inequality - A review - Bennadi Darshana; Kshetrimayum Nandita (Wolters Kluwer Medknow Publications, 2014)
A health disparity (HD) is one of the major public health challenges. The "Healthy People 2020" have got many objectives which includes having access to preventive dental services. Another important activity of "Healthy People 2020" is to monitor health disparities. Oral health is essential to the general health and well-being of individuals as well as for the entire population. Disparities in health among income, racial and ethnic groups are significant. The most powerful factors shaping both health and health disparities are social and economic determinants, or the community conditions for health. [1] This paper reviews health disparity with light on oral health inequalities and its prevention.